Implementasi Inferensi Fuzzy Tsukamoto pada Prediksi Penjualan Telur Ayam Eropa pada Bisnis Raffa Telur - Cici Astria; Harly Okprana; Anjar Wanto; Dedy Hartama; Heru Satria Tambunan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Eggs are an animal product that comes from poultry. Eggs are known as a food that contains nutrients that are very good for the body because they contain a high protein source. Apart from being nutritious, people consume a lot of eggs because the price is relatively cheaper than other protein foods. This research was conducted on the Raffa Egg business located in Pematangsiantar City. The data collection process was carried out by means of interviews and observations with Raffa Eggs. This study aims to predict the number of purchases of European chicken eggs from suppliers. The research was conducted using Tsukamoto fuzzy logic with 3 variables, namely sales (x), inventory (y) and purchases (z). where the sales variable (x) consists of 2 fuzzy sets, including increasing and decreasing, inventory (y) consisting of many and few fuzzy sets and purchasing (z) consisting of many and few fuzzy sets. The results of the calculation of the prediction of the number of purchases of European chicken eggs with sales of 6500 and inventory of 25 000 are 29583 items.Keywords: Eggs, European chicken eggs, Fuzzy, Tsukamoto, Pematangsiantar